1990
DOI: 10.1071/rd9900607
|View full text |Cite
|
Sign up to set email alerts
|

Decreased collagen concentration in rat uterine implantation sites compared with non-implantation tissue at days 6-11 of pregnancy

Abstract: Collagen concentrations at implantation sites in the rat uterus were found to be significantly decreased compared with concentrations in adjacent non-involved uterine tissue in early pregnancy (75% by Day 11). The decrease in collagen was most marked in primary decidua and was also observed to a lesser extent (20%) in myometrium at the implantation site. There was a decrease of 20% in the concentration of total proteins at Day 7 (as measured by the ninhydrin method) and a slight increase in water content (2%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Hydroxyproline concentration was multiplied by a factor of (Woessner, 1962) (1977). Overall, collagen values were similar to those obtained by Myers et al (1990), again confirming that the effects of fixation were minimal.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Hydroxyproline concentration was multiplied by a factor of (Woessner, 1962) (1977). Overall, collagen values were similar to those obtained by Myers et al (1990), again confirming that the effects of fixation were minimal.…”
Section: Introductionsupporting
confidence: 73%
“…Morphological studies have suggested a decline in collagen in the implantation area (Fainstat, 1963;O'Shea, 1983), but the extent of the decline was not measured. Myers et al (1990) (1967). Hydroxyproline concentration was multiplied by a factor of (Woessner, 1962) (1977).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that implantation has evolved from a tissue response to a foreign body [1] and that the uterine response to an invading blastocyst or an artificial deciduogenic stimulus is similar to an inflammatory reaction [2]. The characteristics of the uterine response that are similar to inflammation include an elevated concentration of prostaglandins [3,4], leukotriene (LTB 4 and LTC 4 ) production [5], increased vascular permeability [6], oxygen radical production [7], tissue remodeling [8] including collagen degradation [9], and neutrophil infiltration [10]. Neutrophils have various capabilities that could modify the uterine responses to a blastocyst or deciduogenic stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the more plausible explanation for increased capillary diameter may be that changes in vessel wall components (endothelial cells, basal lamina or both) may result in weakening that allows expansion of the capillaries. There is some evidence that collagen, a component of the vascular basal lamina, is being degraded at this early stage of pregnancy (Myers et al, 1990). In that study, collagen concentrations were significantly lower in implantation sites than in intersite tissue by day 6 of pregnancy.…”
Section: Discussionmentioning
confidence: 80%